PENERAPAN PENDEKATAN TIPOLOGI DAN URBANISME LANSKAP DALAM STRATEGI DESAIN REGENERATIF PEMAKAMAN PERKOTAAN DI TPU MENTENG PULO - Fayola, Aurelia; Ariaji, Priscilla Epifania (Jurusan Arsitektur dan Perencanaan, 2025)
Jakarta faces urban pressure from high population density and limited land availability, while inner-city cemeteries occupy large strategic areas that remain underutilized. Traditionally, public cemeteries (TPU) serve only as passive burial grounds, contradicting their designation as RTH-7, which requires them to function as green spaces, burial sites, social spaces, and sources of revenue. TPU Menteng Pulo exemplifies the complex interplay between land scarcity, burial needs, and untapped ecological potential. This research aims to develop a regenerative design strategy by integrating architectural typology and landscape urbanism principles. The methodology begins with a typological analysis of burial practices based on spatial orientation (horizontal/vertical), burial technology (in-ground, cremation, alternatives), and cultural values. These findings inform the creation of functional zones: Earth (traditional horizontal burial), Mountain (modular vertical structures), and Forest (active landscape). The landscape urbanism approach transforms passive land into multifunctional RTH-7, activating ecological (carbon absorption), social (communal space), and economic (income generation) functions while maintaining the primary burial role. Ultimately, this study offers an applicative framework for managing urban cemeteries in dense areas through a regenerative approach that balances technical, environmental, and socio-cultural aspects. Keywords: burial typology; landscape urbanism; regenerative design; urban cemetery Abstrak Jakarta menghadapi tekanan urban akibat kepadatan penduduk dan keterbatasan lahan, sementara Tempat Pemakaman Umum (TPU) di pusat kota justru menempati area strategis yang luas namun tidak termanfaatkan secara optimal. Selama ini, TPU berfungsi secara pasif sebagai lahan penguburan horizontal tanpa kontribusi aktif terhadap kehidupan perkotaan, sehingga menjadi